Fragment Tracking in Hypervelocity Impact Experiments. (2017) - Watson, Erkai; Gulde, Max; Hiermaier, Stefan
Abstract: Space debris impacts of in-orbit satellites cause varying degrees of fragmentation, ranging from minor damage to catastrophic breakup. In this paper, we introduce an experimental measurement approach for studying the fragmentation effects of hypervelocity impact in the laboratory. We demonstrate this method by investigating a hypervelocity impact on a thin aluminum bumper plates and tracking individual fragments in the debris clouds. The setup involves a thin laser plane illuminating the debris cloud fragments, which are recorded with a high-speed video camera. The image sequence is analyzed, yielding spatio-temporal information about each fragment in the debris cloud. This allows individual fragment size and velocity information, previously not available, to be calculated.